A linear displacement sensor. - Misron, Norhisam; Abdullah, Norrimah; Raja Othman, Raja Nor Firdaus (2009)

(untitled)
A linear displacement sensor (100) used with movable structures is provided, wherein the sensor (100) includes a sensor head (501), wherein the sensor (100) further includes a meandering coil (110), a signal processing unit (120) connectable to the meandering coil (110), a power amplifier (503) connectale to the sensor (100), a pattern guide (130) movable relational to the meandering coil (110), wherein the meandering coil (110)produces an output directly to linear displacement of the movable structure.